Dimensionality and Consequences of Customer Engagement: A Social Exchange Perspective. Issue 3 (September 2019) - Rather, Raouf Ahmad; Sharma, Jyoti
Based on social exchange theory (SET), as well as relationship marketing theory (RMT), this study investigates the impact of customer engagement (CE) underlying dimensions, namely, enthusiasm, attention, absorption, interaction and identification on customer loyalty and affective commitment in hospitality industry. This study also validates and confirms the multidimensionality of CE in hospitality industry. Perceptions of 240 hotel customers were used to explore the relationships. Exploratory factor analysis and confirmatory factor analysis followed by multiple regression analysis were employed to examine the data. The empirical results indicate that by contrasting two rival models, five dimensional model provides the solid foundation and accomplishes excellent fit for data. Empirical results suggest that CE dimensions have influential impact on customer loyalty. Similarly, results demonstrate that CE has significant and positive influence on affective commitment. These findings offer insight into dimensionality and consequences of CE for academic research and bring value to service contexts particularly hospitality.